2014
DOI: 10.1093/schbul/sbu001
|View full text |Cite
|
Sign up to set email alerts
|

Dose Equivalents for Second-Generation Antipsychotics: The Minimum Effective Dose Method

Abstract: This method for determining antipsychotic dose equivalence entails an operationalized and evidence-based approach that can be applied to the various antipsychotic drugs. As a limitation, the results are not applicable to specific populations such as first-episode or refractory patients. We recommend that alternative methods also be updated in order to minimize further differences between the methods and risk of subsequent bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
198
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(203 citation statements)
references
References 76 publications
3
198
0
2
Order By: Relevance
“…No eligible flexible-dose, double-blind trials in acutely ill patients with schizophrenia on iloperidone, lurasidone, and paliperidone were found because no flexible-dose studies comprising the target dose ranges 2 were available (although iloperidone doses could be calculated in the sensitivity analysis). For most drugs, the estimates based on the 3 approaches were comparable with each other and also comparable with those of the "minimum effective dose method" published elsewhere 9 and presented together with 2 methods based on expert consensus 2,3 in Table 1 to facilitate comparison. Supplementary appendix 5 presents the results of the sensitivity analysis (all studies) which, however, showed only very minor discrepancies from the main analyses.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…No eligible flexible-dose, double-blind trials in acutely ill patients with schizophrenia on iloperidone, lurasidone, and paliperidone were found because no flexible-dose studies comprising the target dose ranges 2 were available (although iloperidone doses could be calculated in the sensitivity analysis). For most drugs, the estimates based on the 3 approaches were comparable with each other and also comparable with those of the "minimum effective dose method" published elsewhere 9 and presented together with 2 methods based on expert consensus 2,3 in Table 1 to facilitate comparison. Supplementary appendix 5 presents the results of the sensitivity analysis (all studies) which, however, showed only very minor discrepancies from the main analyses.…”
Section: Resultssupporting
confidence: 75%
“…A major strength is that, compared with other methods, for a number of drugs more data were available. For example, the frequently applied method by Woods 8 (which has been recently updated 9 ) largely depends on how well the minimum effective doses of the various drugs have been identified. As pharmaceutical companies usually conduct only 1 or 2 dose-finding studies, these results are usually based on very limited and partly conflicting data.…”
Section: S Leucht Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…For those drugs for which the article does not provide an algorithm, the World Health Organization’s defined daily doses were used 41. There is no consensus regarding the best way to calculate chlorpromazine equivalents42 and, for sensitivity analyses, the minimal effective doses were used 43…”
Section: Methodsmentioning
confidence: 99%
“…We also defined cases as treatment resistant if during the follow up period they showed little or no symptomatic improvement to two consecutive treatments with antipsychotic medications of adequate dose and duration (at least 6 weeks), even though they were not commenced on clozapine (NICE., 2014). An adequate daily dose of antipsychotic medication was defined according to a daily dose of at least 400mg chlorpromazine equivalence (Leucht et al, 2014). We only included as cases those patients, who failed to respond, and not those who were intolerant of antipsychotic medications or those who self-discontinued medication.…”
Section: Definitions Of Treatment Resistance (Tr)mentioning
confidence: 99%